Pengaruh Struktur Modal dan Likuiditas Terhadap Profitabilitas : (Studi Kasus Perusahaan PT. Matahari Department Store TBK 2019-2023) - Dina Noviana; Murnisa’adatul Jannah; Nida Queena Pratista; Rhamanda Putri (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The purpose of this study is to analyze the influence of capital structure and liquidity on profitability at PT Matahari Department Store Tbk during the 2019-2023 period. A qualitative approach is used in this study. The data used is secondary data in the form of the company's annual financial statements. According to the results of the T test, it shows that the capital structure has a significant influence on profitability of 0.013 (α < 0.05) while liquidity has no significant effect of 0.5944 (α > 0.05). These findings confirm the importance of optimal capital structure management in encouraging company profitability. On the contrary, high liquidity has not been used productively to increase profits. This study recommends an in-depth evaluation of capital and liquidity management strategies to achieve better financial performance.